Impact of Additional Income from the "Family 500+" Program on Household Expenditures - Grzybowska-Brzezińska, Mariola; Doczyk, Karolina Barbara; Kuśmierz, Katarzyna Elżbieta (Studia Oeconomica Posnaniensia, 2018)
The aim of the paper is the identification, analysis and assessment of household income and expenses with special regard to the additional income from the programme "the 500+ Family programme" and its influence on the market behaviour of these households. The research was conducted in October and November 2017, with the number of respondents being 1,700. The research data was collected by sending questionnaires via the Internet and by using the Spearman's rank correlation coefficient for the description of the impact of variables. Among low-income families (in the range of 1,001-2,000 PLN), an increased amount of money spent on the purchasing of food, clothing, and footwear has been reported. Among high-income families (above 4,000 PLN), expenditure on education, clothing and footwear has increased. Besides, the additional income from the programme " the 500+ Family programme" has a direct and positive impact on savings, culture, and entertainment. The findings of this study may lead to specific practical and social recommendations. In the future, it could be recommended to focus on an analysis of income and expenses on particular assortment groups. Moreover, it is also important to concentrate on the families' expenditures with special regard to certain types of services. According to the results of the research, there is a need for further consideration related to household behaviour and the assessment of the quality of life of Polish families with reference to social policy.